SCTN: Event-based object tracking with energy-efficient deep convolutional spiking neural networks - Ji, Mingcheng; Wang, Ziling; Yan, Rui; Liu, Qingjie; Xu, Shu; Tang, Huajin (Frontiers in Neuroscience, 2023)
Event cameras are asynchronous and neuromorphically inspired visual sensors, which have shown great potential in object tracking because they can easily detect moving objects. Since event cameras output discrete events, they are inherently suitable to coordinate with Spiking Neural Network (SNN), which has a unique event-driven computation characteristic and energy-efficient computing. In this paper, we tackle the problem of event-based object tracking by a novel architecture with a discriminatively trained SNN, called the Spiking Convolutional Tracking Network (SCTN). Taking a segment of events as input, SCTN not only better exploits implicit associations among events rather than event-wise processing, but also fully utilizes precise temporal information and maintains the sparse representation in segments instead of frames. To make SCTN more suitable for object tracking, we propose a new loss function that introduces an exponential Intersection over Union (IoU) in the voltage domain. To the best of our knowledge, this is the first tracking network directly trained with SNN. Besides, we present a new event-based tracking dataset, dubbed DVSOT21. In contrast to other competing trackers, experimental results on DVSOT21 demonstrate that our method achieves competitive performance with very low energy consumption compared to ANN based trackers.